Personal networks and desistance from crime in young offenders - Martí, Joel (European journal of criminology, 2021)
In this article we analyse the structure, composition and relational resources of young offenders’ personal networks in order to identify how they are related to desistance. We present a mixed-methods analysis of a sample of young offenders, either in juvenile custody or on probation in Catalonia’s juvenile justice system. We first construct a typology of personal networks according to their composition and structure. In each of the profiles we conduct a qualitative analysis in order to identify the role of relational resources in desistance processes and the meaning that desisters give to these resources. Results show the different relevance of strong and weak ties according to the characteristics of the network and explain how these ties may contribute to the process of desistance.